1976
DOI: 10.1111/j.1365-2389.1976.tb01977.x
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Polyacrylamide to Replace Carbon in the Determination Of‘olsen's’extractable Phosphate in Soil

Abstract: Summary The addition of 2.5 mg/l of polyacrylamide to 0.5M NaHCO3 used as an extractant for ‘available’ phosphate overcame most of the analytical difficulties associated with the use of activated carbon which was recommended in the original procedure of Olsen et al. (1954). No significant differences in the amount of P extracted were found between polyacrylamide and carbon and with the former, technical problems were greatly reduced. Consequently, the modification of the original method to incorporate polyacry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 2 publications
(4 reference statements)
0
16
0
Order By: Relevance
“…Secondly, the exact procedures used by different laboratories for the same nominal method might be somewhat different (extraction time, soil-extractant ratio, filter paper quality, filtering time, etc.). For example, the Danish extraction method uses a slightly modified Olsen Method suggested by Banderis et al (1976) and described in detail in Sørensen & Bu¨low- Olsen (1994). Fotyma et al (2008) and Neyroud & Lischer (2003) have already identified this problem.…”
Section: P Fertilizer Methods In Europe 423mentioning
confidence: 99%
“…Secondly, the exact procedures used by different laboratories for the same nominal method might be somewhat different (extraction time, soil-extractant ratio, filter paper quality, filtering time, etc.). For example, the Danish extraction method uses a slightly modified Olsen Method suggested by Banderis et al (1976) and described in detail in Sørensen & Bu¨low- Olsen (1994). Fotyma et al (2008) and Neyroud & Lischer (2003) have already identified this problem.…”
Section: P Fertilizer Methods In Europe 423mentioning
confidence: 99%
“…Concentrations of hydrolysable amino acids were determined for each fertilizer treatment on a composite HA sample pooled from HA extracted from the field replicates. (Watanabe & Olsen, 1965;Banderis et al, 1976).…”
Section: Humic Acid Characterizationmentioning
confidence: 99%
“…The Olsen method, as modified by Banderis et al (1976), was used for the extraction. The Murphy and Riley (1962) method of P determination was used, in which the concentration of the blue complex produced by the reduction (with ascorbic acid) of the phosphomolybdate formed when acid ammonium molybdate reacts with phosphate is measured by UV-visible spectrophotometry (Pye Unicam model SP6-550) at 880 nm.…”
Section: Phosphorus Availability Determinationsmentioning
confidence: 99%